Analisis Kinerja Keuangan Daerah Propinsi Jawa Tengah serta Implikasinya terhadap Penggalian Potensi Pendapatan Asli Daerah - Kuntari, Yeni (STIE Widya Manggala, 2008)
This research discusses the analysis of financial performance in central java province in 2005. The indicator of financial performance such as regional income ratio to national budget, regional income ratio bruto regional domestic income, Lease ratio and regional retribution to original income, and per capita original income. The population in this research is all towns and sub-provinces in central java provinces. Then at the same time 4 sub-provinces and 4 towns are as samples. So the amount of sample in this research is 8 town or sub-provinces, whose sample has complete financial statement data in 2005. Sampling technique which is used in this research is purposive-judgement convience sampling. The method of data collecting is book study and documentation study. Comperisor analysis is used to compare between financial performance of town or sub-province in central java province so it can be known which town or sub-province has low or high performance. The analysis showed that high financial performance in central java province is Surakarta. While low financial performance in central java province is Pekalongan. The result of this research also give recommendation that region must explore it’s potential original income.